1997
DOI: 10.1530/jrf.0.1090165
|View full text |Cite
|
Sign up to set email alerts
|

Studies in vivo and in vitro on the initiation of follicle growth in the bovine ovary

Abstract: Histological sections prepared from cortical parts of 25 bovine ovaries were used to study initiation of follicle growth in vivo. Small follicles were measured and characterized. Initiation of follicle growth consisted of two distinct consecutive phases. The first phase was characterized by transformation of granulosa cells from a flattened to a cuboidal shape and by their proliferation. In the second phase an increase in the number of granulosa cells was accompanied by a rapid increase in the size of the oocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
127
1
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(146 citation statements)
references
References 26 publications
(33 reference statements)
17
127
1
1
Order By: Relevance
“…The histological analysis of preantral follicles present in the controls as well as in fragments stored at 4 or 20°C showed that changes at the oocyte level constitute the first observed degenerative sign. Similar results were also observed with fresh ovine (Jorio et al, 1991) and caprine (Lucci et al, 1999b) preantral follicles, cold stored at 4°C feline preantral follicles (Wood et al, 1997) and cultured bovine preantral follicles in vitro Braw-Tal andYossefi, 1997). These results show that the oocyte is much more sensitive to degeneration than granulosa cells.…”
Section: Discussionsupporting
confidence: 82%
“…The histological analysis of preantral follicles present in the controls as well as in fragments stored at 4 or 20°C showed that changes at the oocyte level constitute the first observed degenerative sign. Similar results were also observed with fresh ovine (Jorio et al, 1991) and caprine (Lucci et al, 1999b) preantral follicles, cold stored at 4°C feline preantral follicles (Wood et al, 1997) and cultured bovine preantral follicles in vitro Braw-Tal andYossefi, 1997). These results show that the oocyte is much more sensitive to degeneration than granulosa cells.…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, the ontogeny of formation of the ZP was similar to that in cows (Braw-Tal andYossefi, 1997 andFair et al, 1997b) and ewes (Lundy et al, 1999), in which it appeared as islands of zonal material in secondary follicles with two to three layers of granulosa cells and as a complete PAS-positive ring in follicles with more than three layers of granulosa cells (Fig. 7).…”
Section: Discussionsupporting
confidence: 79%
“…Progressive accumulation of fluid will induce distension and coalescence of the lacunae and result in formation of the antrum in antral follicles. In addition, in goat, the formation of the theca appears to be similar to that in cattle (Braw-Tal and Yossefi, 1997) and sheep (Lundy et al, 1999).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…. 1997Braw-Tal and Yossefi, 1997;Sanchez and Ocampo, 1998;Felipe et al, 1999;Zitny et al, 2004;Reynaud et al, 2009;Songsasen et al, 2009). This also showed that folliculogenesis occurs in prepuberal females as reported by Lundy et al (1999) probably mediated by independient gonadotrophin stimuli or by basal levels (Van Vooris, 1999;Evans, 2003).…”
Section: Discussionmentioning
confidence: 99%